Variabilitas Spasio-temporal Terrestrial Water Storage dan Groundwater Storage di Pulau Papua Menggunakan Satelit GRACE dan GRACE-FO - Daniar Ihza Carundyatama; Krisna Dwi Oktabrian; Farrel Fitria Nathania Kuncara; Purwanti Lelly Sabrina; La Ode Ashamad Nusriah (Institut Teknologi Sepuluh Nopember, 2026)
Papua Island represents a region with complex hydrological characteristics influenced by mountainous topography and equatorial tropical climate conditions. This study aims to analyze the spatial, temporal, and seasonal variability of Total Water Storage (TWS) and Groundwater Storage (GWS) across Papua Island during the period 2005–2024 using GRACE and GRACE-FO satellite data integrated with Global Land Data Assimilation System (GLDAS) outputs. The analysis includes spatial mapping of TWS distribution for selected representative years, time-series evaluation across three sub-regions (West Papua, North Papua, and South Papua), and estimation of GWS using the residual approach. The results indicate strong spatial heterogeneity in TWS distribution, with higher storage consistently observed in West Papua and North Papua compared to South Papua. Temporally, TWS shows a positive increasing trend across all sub-regions, with the highest rate observed in West Papua at +0.43 cm/year. GWS variations exhibit a positive long-term trend of +0.38 cm/year and a clear seasonal recharge–depletion cycle, with recharge occurring during June–November and depletion during December–May. These findings demonstrate that GRACE and GRACE-FO observations provide an effective approach for monitoring regional terrestrial and groundwater storage changes, particularly in tropical regions with limited in-situ hydrological observations.